2006
DOI: 10.1159/000094884
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mediators of α<sub>v</sub>β<sub>3</sub>-Induced Endothelial Cell Survival

Abstract: The αvβ3 integrin interaction with the extracellular matrix (ECM) plays an essential role in inhibiting apoptosis in endothelial cells. We have recently shown that αvβ3 ligation on rat aortic endothelial cells (RAECs) specifically activates the transcription factor nuclear factor ĸB (NF-ĸB) and promotes cell survival. Inhibiting NF-ĸB nuclear translocation abolished the protective effect of αvβ3 ligands. Here, we report that ligation of αv<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 153 publications
0
15
0
1
Order By: Relevance
“…Earlier reports suggested that OPN regulates avb 3 integrin mediated NF-kB activation in various cancer and endothelial cells (20)(21)(22)(23)(24)47). The integration of signaling by c-jun Nterminal kinase (JNK) and p38 MAPK plays crucial role in the development of many cancers (48).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports suggested that OPN regulates avb 3 integrin mediated NF-kB activation in various cancer and endothelial cells (20)(21)(22)(23)(24)47). The integration of signaling by c-jun Nterminal kinase (JNK) and p38 MAPK plays crucial role in the development of many cancers (48).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-apoptotic effects of OPN have also been reported for endothelial cells and are mediated through the activation of NF-kB [47,48].…”
Section: Osteopontinmentioning
confidence: 96%
“…OPN signaling through the αvβ3 integrin can modulate (via activation of ras and src) the phosphorylation of kinases (NIK, IKKβ) involved in NFκB activation (Rice et al, 2006, Scatena et al, 1998; this results in the degradation of IκB, an inhibitor of NFκB (Vejda et al, 2005). NFκB regulates expression of many inflammatory cytokines.…”
Section: Signaling Pathwaysmentioning
confidence: 99%